Engine shutdown: migrastatic strategies and prevention of metastases - Raudenská, Martina; Petrláková, Kateřina; Juriňáková, Tamara; Leischner Fialová, Jindřiška; Fojtů, Michaela; Jakubek, Milan; Rösel, Daniel; Brábek, Jan; Masařík, Michal (Trends in cancer, 2023)
Most cancer-related deaths among patients with solid tumors are caused by metastases. Migrastatic strategies represent a unique therapeutic approach to prevent all forms of cancer cell migration and invasion. Because the migration machinery has been shown to promote metastatic dissemination, successful migrastatic therapy may reduce the need for high-dose cytotoxic therapies that are currently used to prevent the risk of metastatic dissemination. In this review we focus on anti-invasive and antimetastatic strategies that hold promise for the treatment of solid tumors. The best targets for migrastatic therapy would be those that are required by all forms of motility, such as ATP availability, mitochondrial metabolism, and cytoskeletal dynamics and cell contractility.
Keywords: pohyb buněk; cancer therapy; Cell Movement; metastasis; nádory; lidé; Neoplasms; cell migration; migrastatic therapy; mitochondria-targeting therapy; Humans; cancer; nanocarriers